Sensitivity Analysis on the Financial Feasibility of CV Dewi Makmur’s Herbal Tea Bag Agroindustry in Bantul, Yogyakarta - Saprilia, Dwi Mutia; Senjawati, Nanik Dara (Jurnal Dinamika Sosial Ekonomi, 2025)
Herbal tea bags have become a major trend in the functional food industry, with increasing domestic demand. CV Dewi Makmur, a producer of herbal tea bags established in 2008 that produces more than 4,000 units per month, faces challenges due to fluctuations in raw material prices caused by seasonal and weather changes. These fluctuations have the potential to affect the company's profitability and long-term sustainability. Therefore, this study aims to analyze the impact of changes in raw material prices on the feasibility of the herbal tea bag agroindustry at CV Dewi Makmur through sensitivity analysis. This research employs a descriptive method with a quantitative approach and a case study design. The respondent selection was conducted using purposive sampling, utilizing both primary and secondary data sources. Data collection techniques included Focus Group Discussions (FGD), observations, and documentation. The data analysis involved calculating the Sensitivity Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), and Profitability Index (PI). The results indicate that the herbal tea bag agroindustry at CV Dewi Makmur remains financially feasible and is not sensitive to an 8% increase in raw material prices. This is supported by a Payback Period of 2 years, 3 months, and 3 days; a Net Present Value (NPV) of IDR 172,860,981; an Internal Rate of Return (IRR) of 58.47%; and a Profitability Index (PI) of 1.20. The study concludes that despite the rise in raw material prices, the business remains profitable and resilient.